V2 O5 Textile Cathodes with High Capacity and Stability for Flexible Lithium-Ion Batteries - Zhu, Yujing (Advanced materials (Deerfield Beach, Fla.), 2020)
© 2020 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.